The impact of artificial intelligence on predicting future government expenditures An applied study in the departments of Nineveh Governorate. (Al-Mansour Journal, 2025)
The research aims to study the impact of artificial intelligence on predicting future government expenditures in Iraq. The study covered 11 directorates in Ninawa province, and the research strategy was a case study of archive data for previous years of Ninawa province departments. The study used the artificial intelligence algorithm represented by the Perceptron network to predict the values of expenditures for future years. The research concluded that the use of artificial intelligence leads to rationalizing and improving spending in government units in Iraq. The researcher recommended encouraging government units to allocate financial resources to implement artificial intelligence technologies, including updating systems, programs, and devices used.
Keywords: artificial intelligence; government expenditures; prediction of government expenditures